On the Development of Resistance against the Corona Policy of the German Government (Global Journal of Human-Social Science, 2023)
Not a day goes by without news on tv radio or internet regarding the growing resistance of many Germans against the corona policy of the German government Recent months show that in Germany the development of resistance movements against the corona policy of the German government has become a problem Indeed there have been types of resistance movements since the beginning of the pandemic in the early 2020 but nowadays it appears as if resistance movements have massively increased People meet for walks through cities each Monday to express their resistance and thus policymakers as well as the police have got a lot of work to ensure and establish order It could be observed that at the beginning of the pandemic during the first lockdown in Germany people s resistance was more or less directed towards corona mitigation measures such as the lockdown policy Nowadays things have changed and people s resistance is mainly aimed at the restrictions against unvaccinated people and the debate about a general compulsory vaccination for all inhabitants The present paper gives an overview on the development of the resistance movement in the Federal Republic of Germany and investigates the reasons for such movements
Keywords: corona policy; pandemic; resistance; trust; resistance movement; compulsory vaccination; restrictions